Patellofemoral Osteoarthritis: Patellofemoral Arthroplasty - Iranpour,F; Aframian,A; Cobb,JP (2019)
Patellofemoral osteoarthritis is common in older people and those with risk factors including trochlear dysplasia and patellofemoral instability. Patellofemoral arthroplasty (PFA) is indicated in such patients and has the advantage of leaving the remaining structures of the knee intact, including the native tibiofemoral joint surfaces and cruciate ligaments. The design of PFA has evolved from inlay designs to onlay designs which are either symmetrical or asymmetrical, to match the native trochlea. Long-term survival of currently used implants is suboptimal, with the largest series of the most commonly used implant reporting a 10-year survival of 77.3% at 10 years, with most patients being revised for progression of disease. Improvements in our understanding of the indications for PFA together with improvements in the design of instruments and instrumentation have the potential to improve the survival of PFA in the future, allowing more people to benefit from the advantages it confers over total knee arthroplasty (TKA).